The Japanese question: An Arendtian analysis of political public space in postwar Japan - Mori, Yaya (Curtin University, 2015)
The Japanese question – the political question of the foundation to Japan’s body politic –remains pending, rather than being totally extinguished in the minds of postwar Japanese citizenry, because freedom can be secured only by what this thesis calls enduring measures of culture, tradition, ritual and authority. Hannah Arendt’s political thought offers an alternative analytical scope for the political public space of postwar Japan, which has been dominated by Marxist discourse and their historiography.